Development of Synchronized Logistics Scenarios - Torres, Diamantino; Xambre, Ana Raquel; Teixeira, Leonor (International Journal of Industrial Engineering and Management, 2016)
Internal Logistics is the industrial department responsible, within an organization, for overseeing the information flow and for controlling the physical movements of materials in the warehouse, factory and between workstations. Currently the improvement of Internal Logistics processes is a key factor for delivering products to customers on time and at a competitive price. There is an increasing need for eliminating non-value added tasks and reducing operating costs. In this context, the synchronization of supply routes is very important in order to create standards and improve the use of resources. The purpose of this study is to describe the way Logistics Scenarios were developed in an industrial environment and also to show the importance of Internal Logistics. Article history: Received (05.03.2015); Revised (16.05.2015); Accepted (22.11.2015)